Comparative Transcriptomics of Alternative Developmental Phenotypes in a Marine Gastropod. Issue 3 (19th May 2016) - Lesoway, Maryna Pauline; Abouheif, Ehab; Collin, Rachel
ABSTRACT: Alternative phenotypes are discrete phenotypic differences that develop in response to both genetic and environmental cues. Nutritive embryos, which arrest their development to serve as nutrition for their viable siblings, are an example of an alternative developmental phenotype found in many animal groups. Females of the marine snail, Crepidula navicella, produce broods that consist mainly of nutritive embryos and a small number of viable embryos. In order to better understand the genetic mechanisms that lead to the development of alternative phenotypes in this species, we compared the transcriptomes of viable and nutritive embryos at the earliest stage that we were able to distinguish visually between the two. Using high‐throughput Illumina sequencing, we assembled and annotated a de novo transcriptome and compared transcript levels in viable and nutritive embryos. Viable embryos express high levels of transcripts associated with known developmental events, while nutritive embryos express high levels of apoptosis‐related transcripts. Gene Ontology term enrichment with GOSeq found that these are associated with the negative regulation of apoptotic processes. This enrichment, combined with morphological evidence, suggests that apoptosis is important in the formation of gastrula‐like nutritive embryos. Apoptosis has been implicated in the development of alternative phenotypes in other animal groups, raising the possibility that this mechanism's role in alternative phenotypes is conserved in gastropod development. We suggest possible alternative mechanisms of nutritive embryo development. Most importantly, we contribute further evidence to the hypothesis that nutritive embryos are an alternative developmental phenotype.